Comparison of Muscle Density in Middle-Aged and Older Chinese Adults Between a High-Altitude Area (Kunming) and a Low-Altitude Area (Beijing) - Liu, Xingli; Wang, Ling; Gao, Meng; Wang, Gang; Tang, Kai; Yang, Jin; Song, Wei; Yang, Jingsong; Lyu, Liang; Cheng, Xiaoguang (Frontiers in Endocrinology, 2021)
Background and Purpose: A high altitude environment was known to have a negative effect on bone and lead to a higher incidence of hip fracture. However, the dependence of muscle composition on altitude is unclear. Thus, we aimed to compare muscle density and area in plateau and low altitude area and to determine the effect of the altitude on these outcomes. Methods: Community dwelling adults over 60 years old living in Beijing (elevation 50 m; 300 subjects,107 men and 193 women) or Kunming (elevation 2000 m; 218 subjects,83 men and 135 women) for more than 10 years were enrolled. Quantitative CT were performed in all subjects and cross-sectional area and attenuation measured in Hounsfield units (HU) were determined for the trunk, gluteus and mid-thigh muscles. Results: Compared to Beijing, Kunming adults were slimmer (Beijing men vs Kunming men: 25.08±2.62 vs 23.94±3.10kg/m2, P=0.013; Beijing women vs Kunming women: 25.31±3.1 vs 23.98±3.54 kg/m2, P= 0.001) and had higher muscle density in the L2-trunk and gluteus maximus muscles after adjustment for age and BMI (L2-trunk muscles: Beijing men 29.99±4.17 HU vs Kunming men 37.35±4.25 HU, P< 0.0001; Beijing women 27.37±3.76 HU vs Kunming women 31.51±5.12 HU, P< 0.0001; Gluteus maximus muscle: Beijing men 35.11 ±6.54 HU vs Kunming men 39.36±4.39 HU, P= 0.0009; Beijing women 31.47±6.26 HU vs Kunming women 34.20±5.87 HU P=0.0375)). Age was similar in both cohorts and no differences were observed in the gluteus medius and minimus muscle or the mid-thigh muscle, either in area or density. Conclusions: Compared with Beijing, the adults in Kunming had higher muscle density of the gluteus maximus and L2 trunk muscles, showing that living at higher altitude might be beneficial to muscle quality.